Electrochemiluminescence Quenching by Halide Ions at Bipolar Electrodes. Issue 3 (31st August 2015) - Fan, Sanjun; Shannon, Curtis
Abstract: Quenching of Ru(bpy)3 2+ electrochemiluminescence (ECL) by Cl −, Br −, and I − ions was studied as a function of halide concentration in a bipolar electrochemical cell. All of the halides investigated showed similar qualitative behavior: above a critical concentration, ECL intensity was found to decrease linearly as the halide ion concentration was increased, due to dynamic quenching of Ru(bpy)3 2+ ECL. Stern‐Volmer slopes (KSV ) of 0.111±0.003, 4.2±0.3, and 6.2±0.3 mM −1 were measured for Cl −, Br − and I −, respectively. The magnitude of KSV correlates with halide ion oxidation potential, consistent with an electron transfer quenching mechanism. Using the bipolar platform described herein, aqueous, halide‐containing solutions could be quantified rapidly using the sequential standard addition method. The lower detection limit is determined by a complex mechanism involving the competitive electrooxidation of halide ions and the ECL co‐reactants, as well as the passivation of the surface of the bipolar electrode, and was found to be 0.20±0.01, 0.08±0.01 and 10±1 mM, respectively, for I −, Br −, and Cl − . The performance of the bipolar ECL quenching assay is comparable to previously published fluorescence quenching methods for the determination of halide ions, while being much simpler and less expensive to implement. Abstract :